Factors Determining The Delay Of Tb Diagnosis And Its Effect On The Disease Transmission In Yemen - Aldhubhani, Adel Hamood Noman (2013)
Tuberculosis (TB) still remains a leading cause of mortality and morbidity with an estimation of 8.8 million new cases in the world. The global incidence rate of TB was growing at approximately 1.1% per year and the number of cases at 2.4% per year. Delay in seeking care of TB increase transmission of pulmonary tuberculosis as well as the burden of TB, which remains high in developing countries. This delay in the diagnosis of TB also could result in increased patient morbidity and mortality. However, early diagnosis and immediate initiation of treatment are essential for an effective TB prevention and control. The aim of this study was to evaluate the delay in TB diagnosis and its effect on TB transmission in addition to its effect on prediagnosis cost. The study was carried out in 3 phases in a referral centre of tuberculosis at Sana’a city, Yemen. Phase One was concerned of a general identification of delay problem and its associated factors. Phase Two was aimed to assess the effect of delay on TB transmission among close contacts. In Phase Three, the relation between pre-diagnosis cost and delay diagnosis of TB patients was assessed. About 505 new smears positive TB patients were recruited to this study. All of the 505 were subjected to interview questionnaire. Moreover, 266 close contacts were subjected to Tuberculin Screening Test (TST). This TST tool was used in phase two of this study. The results obtained in Phase One revealed that, median delay was 60 days for total, 30 days for patient and 10 days for health care delay.